Pediatric Ventriculoperitoneal Shunt: Outcome Analysis in a Tertiary Care Center in Nepal - Phuyal, Suman; Rajbhandari, Binod; Pradhanang, Amit B; Sedain, Gopal; Shilpakar, Sushil K; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2020)
Introduction: Ventriculoperitoneal (VP) shunt is a commonly performed neurosurgical procedure in pediatric surgical practice. It results in a dramatic improvement in patient survival and neurological function but is associated with several complications requiring multiple shunt revisions throughout a patient’s lifetime. The main aim of the study was to evaluate the outcome especially complications of shunt surgery at our center. Methods: A single-institutional, retrospective observational study was conducted in 60 operated cases of congenital hydrocephalus with a minimum follow-up for up to 6 months. Parameters for analysis included demographic data, etiology of hydrocephalus, surgery time, and type of complications. Results: Out of 86 patients, 60 patients who fulfilled the inclusion criteria were enrolled in the study. The mean age of the patients at the time of VP shunt placement was 3 months, range from 8 days to 15 years with male preponderance. The majority of the patients belonged to the 0-1-year age group (76.8%). The commonest etiology of hydrocephalus was congenital aqueduct stenosis. Fifteen patients (25%) developed complications within six months follow-up period. Eight patients (13.3%) developed clinical shunt infection with four cases having culture positive. Four (6.67%) had mechanical complications in the form of shunt obstruction. Three patients had ascites, subdural collection, and shunt extrusion from the anus. The shunt related mortality was 1.67%. Conclusion: The shunt infection and obstruction still remain the most important complications. Despite inherent problems, shunt surgery is the procedure of choice until a safer effective alternative is available.